'Te lo tienes que currar': Enacting an Ethics of Care in Times of Austerity. Issue 1 (1st January 2022) - Gutiérrez Garza, Ana P.
ABSTRACT: Amid austerity policies that have retracted welfare programmes and have affected the livelihood of people in Spain, this paper describes how various local practices of care among members of the PAH (Platform for People Affected by Mortgages) work to recuperate social relations morally and practically. I seek to understand the relationship between people's perceptions of social justice and notions of fairness on the one hand and ideas about deservingness on the other. I am interested in exploring who gets to choose and allocate, and how people in the PAH use the collective notion of care to justify their choice. I analyse the conundrums of a movement that struggles to find a balance between individual judgments and the collective good; I aim to show the dilemmas and contradictions of the struggle for social justice.